Organometallics 2 : complexes with transition metal-carbon *p-bonds - Bochmann, Manfred ([S.l.] : Oxford University Press, 1994)
The interaction of transition metals with unsaturated molecules has led to fundamental insights in the nature of the chemical bond which, in turn, has provided the basis of important present-day applications such as transition metal mediated synthesis or homogeneous and heterogeneous catalysis. This slim volume outlines the chemistry and discusses the bonding in of some of the most important classes of organometallic compounds: the complexes of transition metals with Pi-ligands such as alkenes, alkynes, arenes, and cyclopentadienyl and allyl ligands. The material covered follows on from Organometallics I which covers the chemistry of complexes with metal-carbon delta-bonds. Synthetic and reactivity aspects of each class of compounds are illustrated with pertinent examples from the recent chemical literature. Highlighted excursions relate the fundamental chemistry to current synthetic or catalytic applications. Undergraduates, graduate students and lecturers will find this book to be a wonderful resource.